(untitled) (Nigerian Dental Journal, 2025)
Abstract Introduction Treatment duration and cost are integral aspects of orthodontic treatment planning and are required to predict outcomes. Shorter treatment regimens prevent the adverse effects of orthodontic treatment. Contemporary arch wires have properties that potentially shorten orthodontic treatment time. This study aimed to determine the time to alignment of anterior segment crowding with NiTi and CuNiTi arch wires. Methods: A randomized controlled trial carried out at the Orthodontic unit of a tertiary hospital. Thirty-two arches with Little’s Irregularity Index (LII) of ≥ 4mm on anterior permanent teeth were involved in the study. The LII was measured on study models at pre-treatment and after commencement of orthodontic treatment, at each review visit until it reduced to 3.0mm or less. The results were analyzed on the Statistical Package for Social Sciences Chicago Inc. V. with Mann-Whitney U test, Kaplan-Meier methods, the Log rank test and Cox regression at p<0.05. RESULTS: The arches had moderate 22 (34.3%), severe 25 (39.1%) and very severe 17 (26.6%) crowding. The mean time to alignment was 55.69 ± 20.18 days (CuNiti) and 67.19±33.91 days (Niti). The time to resolution of crowding for 50% of the arches was similar for the wires (p =0.07). The resolution of crowding was 0.77 times higher with CuNiTi wires. Arches with initial severe crowding had a 4.56 increase in the time to alignment with every 1 mm increase in their LII (p value ˂0.05). Conclusion The time to alignment of anterior segment crowding with NiTi and CuNiTi arch wires was similar.